Malaria control in an agro-industrial settlement of Rondônia (Western Amazon Region, Brazil) - Juan Miguel Villalobos Salcedo; Erney Plessmann Camargo; Henrique Krieger; Luiz H Pereira da Silva; Luis Marcelo Aranha Camargo (Memorias do Instituto Oswaldo Cruz, 2000)
A malaria control pilot project was developed in the Urupá agro-industrial farm that is situated in the State of Rondônia (Western Amazon Region, Brazil). Around 180 inhabitants had been surveyed for the past five years. The control measures were based on (1) training a community agent to perform on the spot microscopical diagnosis of malaria and to treat the uncomplicated cases of malaria; (2) limiting the use of insecticides to a short period before the high transmission season. This resulted in a significant reduction in the time between the onset of clinical symptoms and specific chemotherapy which fell from 3.5 to 1.3 days. In relation to the previous three reference years the total number of malaria cases was reduced to 50% in the first year and to 25% in the second year. The introduction of these measures coincided with pronounced reduction in the frequency of Plasmodium falciparum infections but this was less marked for P. vivax infections. In the second year of the pilot experiment there was no P. falciparum transmission on the farm. During the last decade there was a general decrease in the endemicity of malaria in the State of Rondônia. The linear regression coefficient values indicate that the decline was more pronounced in Urupá than in the general municipality and that the falciparum malaria API in Urupá farm is significantly lower than in the general municipality of Candeias were the farm is situated.